NO SUCH THING AS A FREE APP: A TAXONOMY OF FREEMIUM BUSINESS MODELS AND USER ARCHETYPES IN THE MOBILE GAME MARKET - Salehudin, Imam; Alpert, Frank, Dr (ASEAN Marketing Journal, 2021)
Manuscript type: Research Paper Research Aims: The Freemium business model is becoming increasingly prominent in the current digital economy. In the mobile game market, total revenue from free to download apps is overtaking those from paid apps. The purpose of this article is to propose a taxonomy that examines and categorises the various types of Freemium business models. Design/methodology/approach: This study uses the qualitative approach of logical partitioning to generate a Freemium business model's taxonomy through systematic observation of the existing business models. Research Findings: The findings identify advertisement and microtransaction as two primary revenue sources for Freemium business models. The taxonomy also reveals different types of in-app purchases, the most dominant Freemium business model in the mobile game market. Further discussion connects the taxonomy to related issues such as user archetypes and 'user flows'. Theoretical Contribution/Originality: This paper conceptualises a novel taxonomy of business model integrating various research streams and differentiating types of freemium business model. This paper also extends the existing archetypes of Freemium users by adding new categories, namely Remoras and Barnacles, to differentiate free users. Finally, this paper proposes a framework of user flows between the free and the paying state, arguing for a nonlinear flow. Research limitation/Implications: The taxonomy addresses freemium business models in the mobile game market. Application of the taxonomy in a broader context will require further study.